Association between the cardiometabolic index and cardiovascular disease risk in patients with cardiovascular-kidney-metabolic syndrome: a cohort study - De-Gang Mo; Tao Liu; Jing-Xian Bai; Min Liu; Qian-Feng Han; Heng-Chen Yao (BMC Cardiovascular Disorders)
Abstract Background The cardiovascular-kidney-metabolic (CKM) syndrome, a concept introduced by the American Heart Association in 2023, emphasizes preventing cardiovascular disease (CVD). The cardiometabolic index (CMI) serves as a comprehensive measure to predict CVD risk and assess cardiovascular metabolic health. This study aims to examine the association between CMI and CVD risk in individuals with CKM syndrome. Methods Data from 5,530 participants aged 45 and older were analyzed using the China Health and Retirement Longitudinal Study (CHARLS) database. CMI was calculated based on triglycerides to high-density lipoprotein cholesterol and waist-to-height ratios. All participants were followed up over a period of 9 years, with the endpoint event being the occurrence of CVD. Cox regression models were used to analyze the association between CMI and CVD risk. Kaplan-Meier survival analysis was employed to demonstrate the differences in CVD risk among different CMI groups. Subgroup analyses were conducted to explore the applicability of CMI in various subpopulations. Results The CMI of participants who experienced CVD was significantly higher than that of participants who did not experience CVD (0.53 vs. 0.45, p < 0.001). In the fully adjusted Cox regression model, CMI is identified as an independent risk factor for the development of CVD in patients with CKM [Hazard Ratio (HR): 1.07, 95% Confidence Interval (CI): 1.02–1.04, p = 0.006]. Kaplan-Meier survival curve indicated that the highest quartile of CMI was associated with the greatest risk of CVD (Log-rank test, p < 0.001). Subgroup analyses indicate that CMI has a stronger association in patients with CKM syndrome at stage 3 (HR = 1.33, 95% CI:1.07–1.64, p = 0.010). Conclusion Elevated CMI is a critical predictor of CVD incidence in individuals with CKM syndrome, especially in advanced stages.